A superhydrophobic/electrothermal synergistically anti-icing strategy based on graphene composite - Wang, Peng; Yao, Tao; Li, Ziqiang; Wei, Weidong; Xie, Qing; Duan, Wei; Han, Huilong (Composites science and technology, 2020)
Surface icing tends to cause serious problems such as flash over and the following blackout accident. Although electrothermal system is the most widely used method, how to solve the re-freeze problem as the melted ice tend to stay on the surface is still a challenge. Here, we introduced a superhydrophobic/electrothermal synergistically anti-icing strategy based on graphene composite. The superhydrophobicity together with the high electrothermal efficiency let the graphene surface dry and clean in the simulated “glaze ice” condition. Although ice accretion would be formed on the surface when the DC voltage was off, the ice could be rapidly removed within 70 s after applying the voltage of 50 V. To enhance the durability of superhydrophobic surface, the hierarchical structure was constructed by the tri-scale nature of inorganic fillers (graphene, carbon nanotubes and silica nanoparticles). Then the hierarchical structure was partially embedded into the substrate by a dissolution and resolidification method. The coupling effect of partially-embedded structure and hierarchical structure led to the superior robustness, which could withstand sandpaper abrasion (500 g load, 8.00 m), the attack of various corrosive liquids, and low/high temperature treatment without losing superhydrophobicity. More remarkably, this graphene superhydrophobic composite retained deicing property even after 30 icing/deicing cycles.